Cementitious binders in the system Mg(OH)2–NaAlO2–SiO2–H2O. (November 2014) - Walling, S. A.; Bernal, S. A.; Kinoshita, H.; Collier, N. C.; Provis, J. L.
Abstract : In this study, binders within the system Mg(OH)2 –NaAlO2 –SiO2 –H2 O were produced and characterised for the potential immobilisation of radioactive Mg(OH)2 sludges derived from the UK Magnox nuclear programme. The formation of zeolites promoted hardening within 24 h, with the structures and compositions of the zeolites dependent on the contents of SiO2 in the systems. Limited consumption of Mg(OH)2 was identified in the binders cured for up to 90 days, except for a hydrotalcite type layered double hydroxide in binders formulated with low SiO2 contents. This study has elucidated that binders within this system can effectively encapsulate high contents of Mg(OH)2 ; however, the reaction of Mg(OH)2 to form binding phases is limited by the content of SiO2 in the system, and occurs primarily at advanced times of curing.